An alternative to perfect competition - Kearney, M (Town and Regional Planning, 2000)
High concentration can result in welfare losses due to excessive profits and prices. This, however, need not always be the case, since high concentration can be caused by factors such as superior performance and efficiency. Contestability is an alternative to competition policy which does not necessarily call for deconcentration. An industry can be contestable whether it consists of one or many firms. In a contestable market prices will equal marginal cost unless it is not economically viable (if revenue does not cover cost). If prices are set equal to marginal cost welfare will be maximized, if prices are set above marginal cost but are Ramsey prices the loss in welfare will be minimized. Contestability is efficient towards promoting welfare and is easier to apply than competition policy.